Boosting 5th Grade Learning Outcomes with Ethnoscience-Based Problem-Based Learning: Meningkatkan Hasil Belajar Siswa Kelas 5 melalui Pembelajaran Berbasis Etnosains dengan Pendekatan Pemecahan Masalah: Studi Eksperimental Kuantitatif - Izzatur Rohmawati; Fitria Wulandari (Academia Open, 2023)
This quantitative experimental research aimed to investigate the influence of the Ethnoscience-based Problem Based Learning (PBL) model on the learning outcomes of 5th grade students. The study employed a one-group pretest-posttest design and included 27 students from SDN Karangbong. The data collection technique involved administering pre-tests and post-tests to assess student learning outcomes. Data analysis was conducted using paired sample t-tests and Eta Square tests. The results revealed a significant improvement in learning outcomes (Sig. [2-tailed] = 0.001 < 0.05), indicating the effectiveness of the Ethnoscience-based PBL model. These findings underscore the potential of this instructional approach in enhancing student learning and have important implications for educators and curriculum developers seeking innovative strategies to promote student engagement and academic achievement. Highlights: The study employed an experimental research design to assess the impact of the Ethnoscience-based Problem-Based Learning model on learning outcomes. The findings revealed a significant improvement in student learning outcomes, indicating the effectiveness of the instructional approach. This research has implications for educators and curriculum developers seeking innovative strategies to enhance student engagement and academic achievement in elementary school settings. Keywords: Ethnoscience, Problem-Based Learning, Learning Outcomes, Experimental Research, Elementary School